Localization of Malaysian zakat distribution: Perceptions of amils and zakat recipients / Hairunnizam Wahid - Wahid, Hairunnizam (2014)

(untitled)
This study attempts to investigate the perceptions of zakat recipients (the end user) and the amil (the implementer) on whether localization of zakat distribution would be a possible solution to address the problem of zakat management in Malaysia. The study is motivated by the findings of previous studies that the Muslim society is still not satisfied with management of zakat distribution. Research questions include the perceptions of amils and zakat recipients on; (a) the localization concept of zakat distribution; (b) the main determinants of zakat localization; (c) the relationship between zakat localization and the quality of life; and the influence of religiosity on the quality of life of zakat recipients;(d) the factor determinants that amils agreed to implement localization, as well as (e) the potential role of the mosque in implementing localization. Data collected using purposive random sampling on a sample of amils and zakat recipients in Malaysia. The respondents were selected from the states of Selangor, Penang, Federal Territory Kuala Lumpur, Malacca, Terengganu and Kedah. The collected data was analyzed using Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) Structural Equation Modeling (SEM), analysis of variance (ANOVA) and logistic regression (LR). The findings of this study show that majority of respondents strongly support the concept of localization of zakat distribution, especially the amils compared to zakat recipients. It also indicates that all variables, namely trust in Islamic institution (input factor), perceived zakat management (process factor), asnaf’s attitude to change and asnaf’s quality of life (output factor) as well as the proposed localization of zakat distribution (opinion factor) have significant relationship amongst the variables. This finding also indicates that the successful implementation of localization is dependent on the importance of the role of the mosque. Finally, this study recommends the role of the mosque should be strengthened from the outset and then, it would facilitate the implementation of the localization of zakat management.